Late-onset hypogonadism - Dudek, Piotr (Prz Menopauzalny, 2017)
In Poland, the number of men over the age of 50 years exceeds 6 million. It is estimated that about 2-6% of this population develops symptoms of late-onset hypogonadism (LOH). In men, testosterone deficiency increases slightly with age. LOH is a clinically and biochemically defined disease of older men with serum testosterone level below the reference parameters of younger healthy men and with symptoms of testosterone deficiency, manifested by pronounced disturbances of quality of life and harmful effects on multiple organ systems. Testosterone replacement therapy may give several benefits regarding body composition, metabolic control, and psychological and sexual parameters.